Two Novel Disease-Causing Mutations in the LDLR of Familial Hypercholesterolemia - Hu, Haochang; Shu, Tian; Ma, Jun; Chen, Ruoyu; Wang, Jian; Wang, Shuangshuang; Lin, Shaoyi; Chen, Xiaomin (Frontiers in Genetics, 2021)
As an autosomal dominant disorder, familial hypercholesterolemia (FH) is mainly caused by pathogenic mutations in lipid metabolism-related genes. The aim of this study is to investigate the genetic mutations in FH patients and verify their pathogenicity. First of all, a pedigree investigation was conducted in one family diagnosed with FH using the Dutch Lipid Clinic Network criteria. The high-throughput sequencing was performed on three family members to explore genetic mutations. The effects of low-density lipoprotein receptor (LDLR) variants on their expression levels and activity were further validated by silico analysis and functional studies. The results revealed that LDLC levels of the proband and his daughter were abnormally elevated. The whole-exome sequencing and Sanger sequencing were used to confirm that there were two LDLR missense mutations (LDLR c.226 G>C, c.1003 G>T) in this family. Bioinformatics analysis (Mutationtaster) indicated that these two mutations might be disease-causing variants. In vitro experiments suggested that LDLR c.226 G>C and c.1003 G>T could attenuate the uptake of Dil-LDL by LDLR. In conclusion, the LDLR c.226 G>C and c.1003 G>T variants might be pathogenic for FH by causing uptake dysfunction of the LDLR.